2016
DOI: 10.1093/aob/mcw081
|View full text |Cite
|
Sign up to set email alerts
|

An ultra-high density genetic linkage map of perennial ryegrass (Lolium perenne) using genotyping by sequencing (GBS) based on a reference shotgun genome assembly

Abstract: The combined genetic map and assembly, combined with another recently released genome assembly, represent a significant resource for the perennial ryegrass genetics community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 47 publications
(84 reference statements)
0
35
0
Order By: Relevance
“…Genetic mapping has recently been used in several projects to position gene coding regions on plant genomes and help build physical genome maps to anchor sequence scaffolds obtained from WGS, e.g. in chickpea (Deokar et al, 2014), melon (Argyris et al, 2015), potato (Xu et al, 2011), ryegrass (Velmurugan et al, 2016), and soybean (Song et al, 2016). Mapping population sequencing and genetic mapping also enabled the generation of more contiguous genome sequence assembly for barley, wheat and sesame genomes (Mascher et al, 2013;Chapman et al, 2015;Wang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic mapping has recently been used in several projects to position gene coding regions on plant genomes and help build physical genome maps to anchor sequence scaffolds obtained from WGS, e.g. in chickpea (Deokar et al, 2014), melon (Argyris et al, 2015), potato (Xu et al, 2011), ryegrass (Velmurugan et al, 2016), and soybean (Song et al, 2016). Mapping population sequencing and genetic mapping also enabled the generation of more contiguous genome sequence assembly for barley, wheat and sesame genomes (Mascher et al, 2013;Chapman et al, 2015;Wang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…SNP data was collected using genotyping-by-sequencing (GbS) from a subset of 149 genotypes of this F2 population (DNA for these 149 individuals had been readily available at the time of GbS work) and a linkage map was constructed using Joinmap 4.1 [ 23 , 24 ] in a similar approach as described by [ 7 ]. For SNP alignments the perennial ryegrass genome by [ 25 ] was used.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, a number of perennial ryegrass mapping populations have been developed over time and probed using different molecular marker systems (e.g. [ 3 , 5 7 ]. Due to the importance of some components in the diet of ruminants, a number of studies have been reported with the goal of identifying linkage regions responsible for the levels of some traits such as individual sugars [ 8 ], crude protein content [ 9 , 10 ], fatty acid and non-polar composition [ 3 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Irish perennial ryegrass breeding program of Teagasc has developed germplasm in which the self-incompatibility system has been broken down and two inbred lines from this material were used to generate the ‘F2 Biomass mapping population’ that has been the basis of several genetic mapping studies phenotyping traits like SI, non-polar metabolites, crown rust resistance and biomass yield ( Anhalt et al, 2008 , 2009 ; Tomaszewski et al, 2010 , 2012 ; Foito et al, 2015 ). Most recently, the population was used to develop a high density, single nucleotide polymorphism (SNP)-based map based on genotyping by sequencing (GBS) in which reads were aligned to a reference assembly generated by Illumina shotgun sequencing of the paternal grandparent ( Velmurugan et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…This ‘F2 Biomass mapping population’ based on ‘cv S24’ by ‘cv Premo’ parental origins has also been used as the starting point for the production of a RIL population via single seed descent, with the ultimate goal of producing a immortalized reference mapping population which could be shared across different research groups. A small collection from the F6 generation of RILs was used to construct a genetic linkage map using a similar GBS-based approach as adopted in Velmurugan et al (2016) to (1) investigate the genomic and genetic constitution of the RILs in terms of features such as recombination rate, (2) the level of heterozygosity, (3) chromosomal blocks inherited by identity by descent, (4) genome wide linkage disequilibrium (LD) patterns, and (5) segregation distortion.…”
Section: Introductionmentioning
confidence: 99%